179k views
0 votes
-3 (e - 6)= 39 please show work

2 Answers

2 votes
Distribute the -3 to both the e and -6 so you'll get

-3e + 18 = 39
(then subtract 18 from both sides)


-3e + 18 = 39
-18 -18

-3e = 21

Divide both sides by -3 so you'll get e = -7
User Jay Kim
by
5.3k points
1 vote

Hey there!


-3(e-6)= 39

First,
distribute


-3(e)
+
-3(-6)
= 39


  • -3(e) = -3e

  • (-3)(-6 = 18)

  • \boxed{-3e+18=39}

Second,
subtract by
18 on each of your sides


  • -3e + 18
    -18
    = 39- 18

  • Cancel: 18 - 18 because it gives you the result of
    0

  • Keep: 39 - 18 because it helps us get closer to our answer ( is a step to find our answer)

  • 39-18=
    21

  • \boxed{-3e = 21}

Third,
divide by
-3 on each of your sides


  • (-3e)/(-3)

  • = (21)/(-3)

  • Cancel: (-3e)/(-3) because it gives you the result of
    -1

  • Keep: (21)/(-3) because it gives you the result of
    e

  • \Boxed{(21)/(-3)= -7 }

Forth, your
answer


  • \Boxed{Answer: e = -7}

Good luck on your assignment and enjoy your day!

~
LoveYourselfFirst:)

User Crwth
by
4.8k points